MEDICINAL PLANTS IN THE PREVENTION OF GOUT ARTHRITIS - Evi Lusiana; Msy Rulan Adnindya; Nia Savitri Tamzil; Kamaluddin Kamaluddin; Dwi Handayani; Gita Dwi Prasasty; Desi Oktariana; Tia Sabrina (Fakultas Kedokteran Universitas Sriwijaya, 2021)
The use of medicinal plants for healing is the oldest form of medicine in the world. Medicinal plants such as ginger, lemongrass, and turmeric have been clinically tested and proven effective in reducing muscle pain, stiffness, and difficulty moving the knee in patients. Medicinal plants are the types of choice that are efficacious as drugs with easy maintenance and relatively low costs. Medicinal plants are a safe alternative to family medicine because they rarely cause side effects and are easy to process and consume to prevent gout arthritis. Some efficacious herbal plants to reduce pain caused by arthritis are ginger, lemongrass, turmeric, thyme (mint), garlic, green tea, and cinnamon. These plants, based on research, have properties as anti-inflammatory or anti-inflammatory in reducing muscle pain and stiffness in gout arthritis.